DEVELOPMENT AND VALIDATION OF STABILITY INDICATING HPTLC METHOD FOR ESTIMATION OF SWERTIAMARIN IN BULK AND DOSAGE FORM - Padh, H.; Parmar, S.; Patel, B. (International Journal of Applied Pharmaceutics, 2017)
Objective: In the present study a novel stability-indicating high-performance thin-layer chromatography (HPTLC) method for quantitative determination of Swertiamarin (SW) in bulk drug and formulation has been developed and validated as per ICH guideline Q2 (R1) for global acceptance of standardized herbal formulations. Methods: HPTLC method is developed and validated using solvent ethyl acetate: ethanol: chloroform (3:2.5:4.5 v/v/v) (Rf of SW 0.65Â±0.04) in the absorbance mode at 243 nm. Various forced degradation conditions were used to check degradation of drug. Results: The method showed a good linear relationship (r2 = 0.9990) in the concentration range 200-700 ng per spot. It was found to be linear, accurate, precise and specific. Conclusion: It can be applied for quality control as well as for stability testing of different dosage forms containing swertiamarin. The developed method is validated as per ICH guideline Q2(R1) for global acceptance of standardized herbal formulations.